Bacteriological Profile and Antibiotic Susceptibility of Blood Isolates in Blood Stream Infections (Medical Forum Monthly, 2024)
ABSTRACTObjective: The current study was aim to analyse Bacteriological Profile and Antibiotic Susceptibility of Blood Isolates in Blood Stream Infections.Study Design: Experimental studyPlace and Duration of Study: This study was conducted at Department of Pathology, Frontier Medical & Dental College, Abbottabad from January 2010 to August 2011.Material and methods: 1056 blood samples were collected aseptically. The positive blood isolates were identified by standard biochemical tests and their antimicrobial resistance patterns were checked using modified Kirby-Bauer method.Results: Blood cultures were positive in 152 (14.39%) cases. Gram negative isolates were predominant with 104 (68.42%) cases, consisting, in decreasing frequency, of Salmonella typhimurium (39, 37.5%), Pseudomonas aeruginosa (23, 22.1%), Escherichia coli (18, 17.3%) and Klebsiella pneumoniae (14, 13.4%). Staphylococcus aureus accounted for 30 (19.7%) cases followed by coagulase negative Staphylococcus aureus (CONS) in 11 (7.23%) cases among gram positive isolates. Gram positive bacteria were highly resistant to amoxicillin while they were sensitive to cefuroxime and aztreonam. Among gram negative organisms, Escherichia coli & Klebsiella pneumoniae were sensitive to ofloxacin while Pseudomonas aeruginosa to cefpirome and ceftazidime.Conclusion: Our study provides important information about the bacteriological profile and antibiotic resistance pattern of blood isolates in blood stream infections. It will help clinicians to choose an empirical antibiotic therapy to treat such infections.